Longitudinal self-directed competence development of university students through self-reflection. Issue 5 (3rd September 2021) - Colomer, Jordi; Serra, Teresa; Gras, M. Eugènia; Cañabate, Dolors
ABSTRACT: This article presents and explores a framework for self-directed competence development (SDCD) for tertiary students to advance conceptual understanding and practical applications of self-development approaches for the critical assimilation of core competences. The study is based on a four-year longitudinal follow-up of science students from four bachelor's degrees in a science faculty. The students reflected on five basic self-development competencies individually, but were supported by continuous tutoring. The nature of student self-development was thereby explored. The analysis was based on the students' perceptions of how the year-to-year longitudinal reflection process on competencies developed in classes generated self-knowledge, connections between experience and knowledge, self-reflection, and self-regulation of competencies. Participants showed a significant increase in their awareness of self-knowledge over the four years, along with a decreasing need for self-reflection and self-regulated acquisition of competencies. It is argued that supporting effective SDCD through reflection results in instruction that may intervene in managing one's emotional reactions to a daily or professional situation, critically increase one's awareness of the practice of self-reflection, and enact processes of self-regulation for one's individual development.